Autobiographical Element in the Form of Nostalgia in Eliot’s Post-Migration Poetic Work: Four Quartets - Tareen, Ameena; Khan, Fouzia Rehman; Ayyaz, Shazia (Pakistan Languages and Humanities Review, 2024)
The study is conducted to explore the autobiographical element found in Eliot’s poetry in the form of nostalgia. The paper focuses on relevant verses of selected poems along with the biography of T.S. Eliot to examine the aspects of Nostalgia in his poetry. These aspects includes “Restorative nostalgia and Reflective" nostalgia. The aspects of nostalgia, that are to be studied in this academic contribution, have been adopted from Boym, Svetlana (2001) “The Future of Nostalgia”, as a theory for the study. Firstly the selected poems are analysed, through contextual frame of data analysis, and then the aspects of nostalgia are deducted. The detailed study of the sample enable the researcher to conclude that almost all the features of restorative and reflective nostalgia are present in his poetry in different moods, and the poet keeps on shifting from restorative to reflective and vice versa.